Identification of DNA and cDNA sequences from selected differentially expressed transcript of sago palm - Norzuria Idayu, Binti Bahari (Universiti Malaysia Sarawak (UNIMAS), 2011)
Sago palm consists of trunking and non trunking types which make the researchers curious to know the differences between them. There were few studies conducted to differentiate the morphology of leaf starch granules, transcripts of RNA and the present study was carried out to isolate the sequences of DNA and cDNA from trunking and non trunking sago palm primarily to distinguish the differences of genes and RNA transcripts of both species. The sequence isolation was done using DNA and cDNA templates. Samples were collected from Pelita Dalat Plantation, Mukah in Sarawak. The result showed that DNA sequences were successfully amplified from trunking sago palm and preceded with cloning whereby the Colony PCR was successfully performed. The analysis of sequences denoted that some portion of the sequences encoded some types of proteins namely AAA-type ATPase family protein and Protein MSP1